Effects of Turmeric Ethanol Extract on Pancreatic Amylase Enzyme in Doxorubicin-Induced Wistar Mice - Wen Shiqi; Florenly Florenly; Johannes Bastira; Fioni Fioni (Budapest International Research and Critics University, 2021)
Type II diabetes mellitus indicates the presence of chronic hyperglycemia and results from progressive failure of pancreatic β cells in which the amount of insulin is insufficient to meet metabolic demands and is characterized by peripheral insulin resistance and impaired insulin secretion. Turmeric (Curcuma longa Linn) has been widely researched and used for antioxidants, antivirals, anti-inflammatories, as well as its potential as a functional food for pancreatic-related diseases. The study's goal was to test the effectiveness of turmeric ethanol extract against pancreatic amylase enzymes in doxorubicin-induced Wistar mice (lowered fasting KGD, 2 hoursPP, HbA1C, in doxorubicin-induced male mice). This type of research is an experimental study, in early March 2021, conducted at the Laboratory of Pharmaceutical Pharmacology of the University of North Sumatra. The animals used in the study were male rats weighing 150–200g. The results in the treatment group iii treatment group (ethanol extract Curcuma longa 600g) had blood sugar levels of 74.2014 ± 3.78 mg/ml had a neggant difference (P<0.05) with the negative control group and did not have a significant difference (P>0.05) with the positive control group. Ethanol extract Curcuma longa doses of 200 mg/kg bb, 400 mg/kg bb, and 600 mg/kg bb had significantly different blood glucose levels decreased activity (P<0.05) with negative control groups given only CMC-Na and doxorubicin. Curcuma longa extract doses of 200 mg/kg bb, 400 mg/kg bb, and 600 mg/kg bb had significantly different hbA1c reduction activity (P<0.05) with negative control groups given only CMC-Na and doxorubicin. Advice, for researchers, can further do antidiabetic testing by looking at insulin expression after doxorubicin-induced and tested measurement of antioxidant levels such as GSH and Catalase.